Fertility trends and comparisons in a historical cohort of US women with primary infertility - Emily Sadecki; Amy Weaver; Yulian Zhao; Elizabeth A. Stewart; Alessandra J. Ainsworth (BMC, 2022)
Plain language summary This study aimed to assemble a historic cohort of women with primary infertility and age-matched control women. The cohort included 1001 women with primary infertility diagnosed between 1980 and 1999 and 1001 age-matched controls from the same community and era. This cohort demonstrated baseline differences between the primary infertility and control groups, including differences in marital status, education, use of barrier contraception and smoking status. Additionally, the cohort showed an increased incidence in diagnosis of primary infertility from 1980 to 1999. Creation of this cohort will enable future research focused on long-term outcomes following primary infertility diagnosis and treatment.